Serological response to vaccination after autologous transplantation for multiple myeloma is associated with improved progression-free and overall survival - Merz, Almuth; Merz, Maximilian; Zhang, Yali; Stecklein, Kathryn; Pleskow, Jordan; Chen, George L.; Buck, Dennis A.; Mohammadpour, Hemn; Herr, Megan M.; Elshoury, Amro; Hillengaß, Jens; McCarthy, Philip L.; et al. (Transplantation and cellular therapy, 2021)
Revaccination after autologous hematopoietic cell transplantation (AHCT) is recommended in post-HCT survivorship guidelines to restore humoral immunity. Data on seroconversion after AHCT and vaccination in multiple myeloma (MM) patients are limited. We investigated the feasibility and effectiveness of vaccination post-AHCT and analyzed the restoration of humoral immunity and patient prognosis. Anti-pathogen titers were measured within a median of 2 days before and 96 days after AHCT and following revaccination in 139 MM patients who had a first AHCT from 2013 to 2016. Most (84%) patients received at least one dose of any planned vaccines. High-dose melphalan with AHCT restored measurable immunity in 18% of patients. In an additional >60% of patients, seroconversion occurred after vaccination; however, despite vaccination, 20% of patients remained seronegative for most pathogens. Attainment of MM complete response post-AHCT was associated with higher rates of seroconversion which yielded significantly longer progression-free and overall survival. Our study demonstrates the feasibility of post-AHCT vaccination, supporting measurement of post-vaccination titers to determine which patients should be considered for antimicrobial prophylaxis, as seroconversion does not occur in all patients. Titer seroconversion is a potential indicator of the immunological effects of AHCT, with restoration of humoral immunity demonstrating improved survival.